Correlation Between Self-Motivation and Family Support on Stress Levels and Self-Acceptance of Type 2 Diabetes Mellitus Patient - Krisnansari, Diah; Wulansari, Rahmawati; Husnannisa, Fadhila (Faculty of Medicine, Public Health, and Nursing, 2024)
Background: Type 2 Diabetes Mellitus patients often have psychological problems related to burdens and worries about their illness, so they need family support as a support system in dealing with existing worries and emotional burdens. Family support will lead to self-confidence and motivation to deal with their problems. Motivation can come from family support and also from the patient's self-motivation. Motivation from family support and self-motivation is related to the patient's stress level and self-acceptance. Objectives: To determine the correlation between self-motivation and family support on stress levels and self-acceptance in type 2 Diabetes patients at Sumbang Banyumas. Methods: The analytic observational study with a cross-sectional approach on 49 respondents with type 2 Diabetes Mellitus used the Hensarling Diabetes Family Support Scale Questionnaire, Treatment Self-Regulation Questionnaire, General Health Questionnaire-12, and Berger's Self-Acceptance Scales. Data were analyzed using the gamma correlation test with α<0.05. Results: The results showed 89.8% were over 45 years old, 83.7% were women, 69.4% were elementary school graduates, 53% were not working, 81.6% had a monthly income below the Regional Minimum Wage, 71.4% had no genetic of Diabetes Mellitus, 34.7% had a long duration of suffering from Diabetes Mellitus < 5 years and 5 - 10 years and 73.5% had good APGAR score, 73.4% had good self-motivation, 69.4% had good family support, 67.3% had mild stress levels and 75.5% had good self-acceptance. There was a significant correlation between self-motivation (p= 0.037) and family support (p= 0.000) on stress levels and there was a significant correlation between self-motivation (p = 0.000) and family support (p = 0.000) on self-acceptance. Conclusions: Self-motivation and family support correlate with stress levels and self-acceptance of type 2 Diabetes Mellitus patients at Sumbang Banyumas.